Two new species of Helicopsyche Siebold 1856 (Insecta: Trichoptera: Helicopsychidae) from Pará State, northern Brazil - Neto, Jaime De Liege Gama; Ribeiro, José Moacir Ferreira; Passos, Mahedy Araujo Bastos (Zootaxa, 2019)
Two new species of Helicopsychidae from Pará State, Brazil, are described and illustrated: male of Helicopsyche (Feropsyche) carajas n. sp. is characterized by segment X having 8 pairs of subequal megasetae distributed in a pair of longitudinal rows; the primary branch of each gonocoxite, in lateral view, with its basal half nearly as broad as its median part and parallel-sided, its posterior apex directed slightly ventrad and slender and strongly pointed; the dorsal lobes of the endotheca posteriorly protruding, and the lateral lobes of the endotheca well developed. Helicopsyche (Feropsyche) inflata n. sp. is characterized by the hind wings each having very long fringes along the anal border; the primary branch of each gonocoxite having a pointed apex in lateral view and its basimesal lobe being triangular in lateral and ventral views and bearing eight megasetae; and the dorsal lobe of the endotheca being very well developed in lateral view.